Double Dirac cones and zero-refractive-index media in water waves. (5th October 2018) - Wu, Shiqiao; Mei, Jun
Abstract: We propose a new design paradigm for the realization of double Dirac cones and zero refractive index in water wave systems. By intentionally modulating the bottom of a water domain in a periodical way, the double Dirac cone dispersion of water wave can be obtained at the Brillouin zone center. We find that the water wave system can be effectively described as a zero-refractive-index medium around the double-Dirac-point frequency. Based on the effective medium theory and through full wave simulations, we unambiguously demonstrate the intriguing transport behaviors of the water wave, including directive emission, beam splitting, object cloaking, and barrier tunneling. Our proposal provides an alternative method for the manipulation and control of water waves in an efficient way.